Factors Associated With Ventriculoperitoneal Shunt Placement in Patients With Cryptococcal Meningitis. (20th May 2019) - Baddley, John W; Thompson, George R; Riley, Kristen O; Moore, Mary K; Moser, Stephen A; Pappas, Peter G
Abstract : Elevated intracranial pressure in patients with cryptococcal meningitis is common and associated with poor outcomes. This study evaluated factors at the time of diagnosis of cryptococcal meningitis that were associated with need ventriculo-peritoneal shunting. Abstract: Objective: Increased intracranial pressure (ICP) is an important complication of cryptococcal meningitis (CM) and impacts morbidity and mortality. Factors associated with permanent ventriculoperitoneal (VP) shunt placement are poorly characterized. Method: We conducted a retrospective cohort study of patients with CM at the University of Alabama at Birmingham from 1996 through 2015. Characteristics of patients at time of CM diagnosis who did and did not receive a VP shunt were compared with use of the 2-group chi-square test or Fisher exact test for categorical variables and the 2-group t test for continuous variables. Stepwise logistic regression analysis was used to determine predictors of shunt placement. Results: Of 422 patients with cryptococcosis, 257 (60.9%) had CM. Mean age was 47.7 years, 71.6% were male, and 44.4% were African American. The most common underlying conditions were HIV (42.4%), solid organ transplantation (29.6%), and corticosteroid use (34.2%). Forty-four (17.1%) received a VP shunt a median of 17 days (range, 1–320 days) post-diagnosis. By multivariable analysis, baseline opening pressure >30 cm H2 O (OR, 9.4; 95% CI, 3.0, 28.8; P < .0001), being a normal host (OR, 6.3; 95% CI, 1.5, 26.1; P = .011) and hydrocephalus (OR, 4.9, 95% CI, 1.3, 17.9); P = .017) were associated with increased odds of shunting (Table 2). In contrast, age (OR, 0.96; 95% CI, 0.92, 0.99; P = .037) and male gender (OR, 0.18; 95% CI, 0.06, 0.55; P = .023) were associated with decreased odds of shunting. Conclusions: Identification of factors at time of CM diagnosis associated with need for permanent VP shunt placement may allow for earlier, more aggressive treatment and potentially improve outcomes associated with increased ICP from cryptococcal meningitis.